The Ratio of 2-AG to Its Isomer 1-AG as an Intrinsic Fine Tuning Mechanism of CB1 Receptor Activation - Dócs, Klaudia; Mészár, Zoltán; Gonda, Sándor; Kiss-Szikszai, Attila; Holló, Krisztina; Antal, Miklós; Hegyi, Zoltán (Frontiers in Cellular Neuroscience, 2017)
Endocannabinoids are pleiotropic lipid messengers that play pro-homeostatic role in cellular physiology by strongly influencing intracellular Ca2+ concentration through the activation of cannabinoid receptors. One of the best-known endocannabinoid ‘2-AG’ is chemically unstable in aqueous solutions, thus its molecular rearrangement, resulting in the formation of 1-AG, may influence 2-AG-mediated signaling depending on the relative concentration and potency of the two isomers. To predict whether this molecular rearrangement may be relevant in physiological processes and in experiments with 2-AG, here we studied if isomerization of 2-AG has an impact on 2-AG-induced, CB1-mediated Ca2+ signaling in vitro. We found that the isomerization-dependent drop in effective 2-AG concentration caused only a weak diminution of Ca2+ signaling in CB1 transfected COS7 cells. We also found that 1-AG induces Ca2+ transients through the activation of CB1, but its working concentration is threefold higher than that of 2-AG. Decreasing the concentration of 2-AG in parallel to the prevention of 1-AG formation by rapid preparation of 2-AG solutions, caused a significant diminution of Ca2+ signals. However, various mixtures of the two isomers in a fix total concentration - mimicking the process of isomerization over time - attenuated the drop in 2-AG potency, resulting in a minor decrease in CB1 mediated Ca2+ transients. Our results indicate that release of 2-AG into aqueous medium is accompanied by its isomerization, resulting in a drop of 2-AG concentration and simultaneous formation of the similarly bioactive isomer 1-AG. Thus, the relative concentration of the two isomers with different potency and efficacy may influence CB1 activation and the consequent biological responses. In addition, our results suggest that 1-AG may play role in stabilizing the strength of cannabinoid signal in case of prolonged 2-AG dependent cannabinoid mechanisms.